KOMPARASI PEMIKIRAN IBNU SINA DAN SUHRAWARDI: (Telaah terhadap Teori Emanasi dan Teori Jiwa) - Muhammad Natsir (Kopertais Wilayah X Jawa Tengah, 2014)
AbstractPhilosophy is an intellectual exercise that allows humans to determine the form as it is in itself. It is the duty of man to do this through the intellectual exercise of his soul so that he is glorified and perfect. It could also be a rational scientist and obtain eternal happiness in the next capacity. Islamic philosophy has an important theme of the study, it includes God, man and nature. The post-modern era, that demands rationality, causes a sharp shift in the human orientation, knowledge and understanding of the ideas of Muslim philosophers becomes a necessity for Muslims to offset the secular world view that can be destructive to the faith, tradition, and the moral nation. The research aims to explain some of the thinking of experts once famous Muslim philosopher in the east, namely Avicenna and Suhrawardi. This research is to explore and describe a second thought to this and subsequent figures and compromise by describing the differences, similarities and simultaneously find the mindset of both. The result of the discussion explains the suitability of the substance and essence of thought these two characters, and different things are in the use of terms and patterns or ways of thought.Keywords: Comparison, Emanation Theory, The Theory of the Soul, Ibn Sina, Suhrawardi.